Good practices in Distance Education and success in a Pedagogy class (Research, Society and Development, 2019)
Distance Education (EAD) continues to expand in Brazilian Higher Education. A recent measure by the Ministry of Education has increased the possibility of increasing distance learning courses from 20% to 40% in face-to-face courses, provided that institutions and courses comply with legal standards. The distance education is an educational modality in which not all the students adapt since it presupposes the student's autonomy in the search and construction of the knowledge, through didactic material and the methodology of the disciplines in promoting the participation of the student in the proposed activities . The question is whether there are ways to overcome the difficulties of this modality? The objective of the present study is to present a study in a distance discipline in which difficulties initially occur in the educational process and these are worked through good practices. A work of research-action is carried out in a discipline of scientific methodology of a Pedagogy course in the southeast region in which the implementation of 20% of EAD was initiated. Initially it is detected the existence of learning difficulties detected by the Evaluation Committee of the students of the course. There is a collaborative work that results in a change in the way of work. It is verified that the students improve their school performance showing that there are cases in which it is possible to improve the learning and satisfaction of the students in this modality.